INTERACTION OF TRADITIONS AND INNOVATIONS IN MODERN MUSIC EDUCATION - Seit-Enon Amide Yusuf qizi (American Journals, 2023)
The article examines the role of traditions and innovations, and also determines the prospects of music education in the formation of a socially and professionally significant personality. The main attention is paid to the constructive nature of the unity of traditions and innovations in music education.
Keywords: Cultural traditions, innovations, modernity, music education, thinking, musical thinking, media technologies.